Antioxidant characterization of soy derived products in vitro and the effect of a soy diet on peripheral markers of oxidative stress in a heart disease model - Hagen, Martine Kienzle (2012)
This study analyzed and compared the content of isoflavones in 2 soy products the effectiveness of isoflavones as antioxidants in vitro and demonstrated the antioxidant effect of a soy diet in rats with myocardial infarction (MI). Isoflavone content was analyzed in soybean hypocotyl (SH) and isolated soy protein (ISP). The quality (TAR) and quantity (TRAP) of antioxidants present in the samples was quantified. The amount of daidzin was higher in SH (9 times) and genistein in ISP (5 times). SH presented a 3-fold increase in TAR while both products exhibited same TRAP. The rats were fed an ISP diet for 9 weeks. Animals were distributed among 6 treatment groups: (i) Sham Casein; (ii) Infarct Casein < 25%; (iii) Infarct Casein > 25%; (iv) Sham Soy; (v) Infarct Soy < 25%; and (vi) Infarct Soy > 25%. MI was induced 5 weeks after the commencement of the diets. Lipid peroxidation (LPO) antioxidant enzyme activity and levels of nitrites/nitrates were determined in blood. Rats receiving the ISP diet demonstrated increased activity of antioxidant enzyme activity and nitrite/ nitrate content. In addition the increase in LPO seen in rats subjected to MI was significantly mitigated when the ISP diet was given. These findings suggest a nutritional approach of using a soy-based diet for the prevention of oxidative-stress-related diseases such as heart failure.